TIGIT: A Novel Entry in NK Cell Regulation - Khatri, Sophia (Midwestern Journal of Undergraduate Sciences, 2022)
While TIGIT’s immunoregulatory role in T Cells has been described, the mechanisms through which TIGIT modulates NK Cell activity has remained elusive. Recent research by Staniesky et al. reveals that the expression of TIGIT by NK cells inhibits the lysis of PVR and PVRL1-expressing target cells in an ITIM-dependent manner.